2016
DOI: 10.3791/54735
|View full text |Cite
|
Sign up to set email alerts
|

High-fat Feeding Paradigm for Larval Zebrafish: Feeding, Live Imaging, and Quantification of Food Intake

Abstract: Zebrafish are emerging as a model of dietary lipid processing and metabolic disease. This protocol describes how to feed larval zebrafish a lipid-rich meal, which consists of an emulsion of chicken egg yolk liposomes created by sonicating egg yolk in embryo media. Detailed instructions are provided to screen larvae for egg yolk consumption so that larvae that fail to feed will not confound experimental results. The chicken egg yolk liposomes can be spiked with fluorescent lipid analogs, including fatty acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…When MTP is mutated or absent, B-lp production is reduced or absent and TG accumulates in cytoplasmic lipid droplets (LDs) [ 54 56 ]. We have previously shown that accumulation of LDs in intestinal enterocytes of zebrafish larvae fed a high-fat meal causes the gut to be opaque [ 57 ] ( S4 Fig ), most likely due to the lipid droplets’ ability to scatter light [ 58 , 59 ]. Therefore, we hypothesized that the yolk opacity in the mttp mutant embryos is due to aberrant accumulation of LDs in the cytoplasm of the YSL.…”
Section: Resultsmentioning
confidence: 99%
“…When MTP is mutated or absent, B-lp production is reduced or absent and TG accumulates in cytoplasmic lipid droplets (LDs) [ 54 56 ]. We have previously shown that accumulation of LDs in intestinal enterocytes of zebrafish larvae fed a high-fat meal causes the gut to be opaque [ 57 ] ( S4 Fig ), most likely due to the lipid droplets’ ability to scatter light [ 58 , 59 ]. Therefore, we hypothesized that the yolk opacity in the mttp mutant embryos is due to aberrant accumulation of LDs in the cytoplasm of the YSL.…”
Section: Resultsmentioning
confidence: 99%
“…From 4 dpf until the last day of treatment renewal—at 9 dpf—larvae were fed daily with a SD, 10% of fat (Tetramin, Tetra, Blacksburg, VA, USA), or with a HFD made of chicken egg yolk, ~53% of fat (Sigma-Aldrich, St. Louis, MO, USA), for 1 h before medium renewal. Both diets were also previously used in zebrafish [ 27 , 100 , 101 ]. At 5 dpf, larvae were exposed with 43 mM ethanol directly added to the incubation medium and/or by 25 nM B[a]P in dimethyl sulfoxide (DMSO)—DMSO final proportion: 0.001% v/v —or by this vehicle only until 12-dpf.…”
Section: Methodsmentioning
confidence: 99%
“…Embryonic feeding assays were performed as previously published (41). Briefly, equal amounts of BODIPY FL C12 (Life Technologies) egg yolk were provided to 7 days post fertilization (dpf) larvae for a period of 4 hours at 28.5 °C.…”
Section: Methodsmentioning
confidence: 99%